Efficacy of turmeric in the treatment of oral mucositis in patients with head and neck cancer after radiotherapy or chemoradiotherapy: a systematic review and meta-analysis - Wu, Chiu-Feng; Wu, Hui-Juan; Shih, Chia-Lung; Yeh, Tzu-Pei; Ma, Wei-Fen (Frontiers in Pharmacology, 2024)
Background: Oral mucositis is a major complication for head and neck cancer (HNC) patients after receiving radiotherapy. Meta-analysis was used to assess the effectiveness of turmeric in treating oral mucositis in HNC patients.Methods: Randomized controlled trials investigating our topic were included in the metaanalysis. The clinical outcomes considered were the severity of oral mucositis, pain level, and weight loss.Results: A total of eight articles met our inclusion criteria were included in our meta-analysis.At the 3-(p = 0.03) follow-up visit, the turmeric group showed significantly lower grades of oral mucositis compared to the control group. When compared to the placebo group, a significant difference in the grades of oral mucositis was observed at the 4-week (p = 0.03) and 6-week (p < 0.00001) follow-up visits. No significant difference in pain level between the turmeric and control group was observed at any follow-up visits. However, a significant improvement in pain level for the turmeric group was only observed at the 6-week followup visit (p = 0.006) when compared with the placebo group. Interestingly, a significant improvement in pain level for the turmeric group was observed at the 2-, 4-, 5-, and 6-week follow-up visits (p < 0.05) when compared with the non-placebo group. The turmeric group had less weight loss than the control group at the final follow-up visit (p = 0.03).Conclusion: Our meta-analysis showed that using turmeric could be effective in improving both the severity of oral mucositis and pain levels in HNC patients who have received radiotherapy or radiochemotherapy. Additionally, the turmeric group experienced less weight loss.